Muscles are barely required for the patterning and cell dynamics in axolotl limb regeneration - Hu, Yan; Pan, Xiangyu; Shi, Yu; Qiu, Yuanhui; Wang, Liqun; Murawala, Prayag; Liu, Yanmei; Xing, Wanjin; Tanaka, Elly M.; Fei, Ji-Feng (Frontiers in Genetics, 2022)
Regeneration of a complex appendage structure such as limb requires upstream and downstream coordination of multiple types of cells. Given type of cell may sit at higher upstream position to control the activities of other cells. Muscles are one of the major cell masses in limbs. However, the subtle functional relationship between muscle and other cells in vertebrate complex tissue regeneration are still not well established. Here, we use Pax7 mutant axolotls, in which the limb muscle is developmentally lost, to investigate limb regeneration in the absence of skeletal muscle. We find that the pattern of regenerated limbs is relative normal in Pax7 mutants compared to the controls, but the joint is malformed in the Pax7 mutants. Lack of muscles do not affect the early regeneration responses, specifically the recruitment of macrophages to the wound, as well as the proliferation of fibroblasts, another major population in limbs. Furthermore, using single cell RNA-sequencing, we show that, other than muscle lineage that is mostly missing in Pax7 mutants, the composition and the status of other cell types in completely regenerated limbs of Pax7 mutants are similar to that in the controls. Our study reveals skeletal muscle is barely required for the guidance of other cells, as well the patterning in complex tissue regeneration in axolotls, and provides refined views of the roles of muscle cell in vertebrate appendage regeneration.